2015
DOI: 10.1021/cg500987c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Thermal Instability of the Cu2Ta4O11 Phase

Abstract: The Cu(I)-tantalate, Cu 2 Ta 4 O 11 , has been synthesized by flux methods in high purity and characterized by singlecrystal X-ray diffraction (space group R3̅ c (167), a = 6.219(2) Å, c = 37.107(1) Å). The compound is a new n = 1 member of the Cu(I)-tantalate Cu x Ta 3n+1 O 8n+3 series of structures and can be prepared in a molten CuCl flux within a relatively low temperature range of ∼625−700 °C, in comparison to the synthesis of Cu 5 Ta 11 O 30 (n = 1.5) and Cu 3 Ta 7 O 19 (n = 2) at ∼800 to 1000 °C. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…For example, when Cu 2 Ta 4 O 11 is heated in a vacuum, the following decomposition occurs: Cu 2 Ta 4 O 11 → Cu 2 O + 2 Ta 2 O 5 . This reaction, and other alternative decomposition pathways, have been observed in all Cu(I)-containing niobates, tantalates, and vanadates [4][5][6][15][16][17][18]. For example, Cu 2 Ta 4 O 11 is calculated to be metastable by ~0.04 eV atom −1 , and thus its decomposition reaction is thermodynamically favorable.…”
Section: Introductionmentioning
confidence: 84%
“…For example, when Cu 2 Ta 4 O 11 is heated in a vacuum, the following decomposition occurs: Cu 2 Ta 4 O 11 → Cu 2 O + 2 Ta 2 O 5 . This reaction, and other alternative decomposition pathways, have been observed in all Cu(I)-containing niobates, tantalates, and vanadates [4][5][6][15][16][17][18]. For example, Cu 2 Ta 4 O 11 is calculated to be metastable by ~0.04 eV atom −1 , and thus its decomposition reaction is thermodynamically favorable.…”
Section: Introductionmentioning
confidence: 84%
“…Computational studies have found that structural rigidity and inhibited ion mobility are key to the strong kinetic stabilization of metastable phases . One example is given by Cu 2 Ta 4 O 11 → Cu 2 O + 2Ta 2 O 5 . After removal of the CuCl flux used in the synthesis of Cu 2 Ta 4 O 11 , the high mobility of Cu­(I) cations (with ∼33% site vacancies) leads to the slow decomposition reaction at its surfaces at even room temperature.…”
Section: Mixed-metal Oxide (M′mo X ) Semiconductorsmentioning
confidence: 99%
“…The Cu 2 Ta 4 O 11 structure occurs in two polymorphs, namely, the monoclinic α-Cu 2 Ta 4 O 11 phase and the rhombohedral β-Cu 2 Ta 4 O 11 [64,65], shown in Figures 5 and 6. At temperatures of −50 • C to room temperature, the monoclinic α-Cu 2 Ta 4 O 11 phase is relatively stable.…”
Section: Cu 2 Ta 4 O 11mentioning
confidence: 99%
“…The linearly coordinated Cu cation and 7-coordinate Na cation are located at the 18d and 12c Wyckoff crystallographic sites, respectively. By comparison, the use of nanoparticle reactants and lower reaction temperatures of ≈625 • C to ≈700 • C were found necessary to obtain the Cu-richest composition, i.e., Cu 2 Ta 4 O 11 , in high crystalline purity [65]. This composition was found to undergo a transformation from a monoclinic structure (Cc) to a rhombohedral (R3c) crystal structure upon heating, i.e., from α-Cu 2 Ta 4 O 11 to β-Cu 2 Ta 4 O 11 , as described above [64].…”
Section: Niobates/tantalates Solid Solutionmentioning
confidence: 99%
See 1 more Smart Citation